Liberalizaç\~ao do comércio de serviços: O caso do setor de telecomunicaç\~oes no Brasil - Pedro Miranda; Honorio Kume; Guida Piani (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper describes the process of trade liberalization in the telecommunications industry implemented from the mid-1990s and examines how such a measure, which allowed foreign capital an important role in the control of operators, associated with the privatization program affected the performance and structure market this activity. As a result the investments increased from 5.2% of gross capital formation in 1996 to 10% in 2001, then decreased reaching around 3% in 2009, with foreign direct investment of US 41 billion. The number of accesses in services between 1996 and 2009 has increased in fixed telephony 14 million for 41 million, in mobile telephony 3 million to 174 million and in broadband 1 000 to 11 million. In the period 2005-2009, there was a fall in the real price of around 7%. However, not all goals were achieved mainly at the level of competition among operators.
Keywords: F14; 330; Telekommunikation; Handelsliberalisierung; Brasilien